Present Uncertainty and Looking to the Past: The Ambiguous Literary Nationalism of Putnam’s Monthly - Mark NIEMEYER (E-REA)
Putnam’s Monthly (1853-1857) was one of the best literary and general interest magazines in antebellum America. Besides its high quality, what made the New York-based magazine stand out was its commitment to publishing American writers and focusing on American themes at a time when, with no reliable international copyright protection in place, many periodicals in the United States were in the habit of reprinting the works of foreign (primarily British) authors, sometimes without payment. However, despite its optimistic literary nationalism, Putnam’s Monthly expressed uncertainty about the quality of contemporary American literature and, indeed, about the capacity of American society to encourage cultural pursuits. And when the magazine looked towards the nation’s past—an important theme for literary nationalists—there, too, its view of the United States seemed uncertain. And the magazine also made an almost desperate attempt to paint a positive picture of the nation’s literary situation in part by exploiting a certain vagueness created by the evolving definition of the term “literature.” This article explores some of the ambiguities created by the tension between the editorial policy of literary nationalism adopted by Putnam’s Monthly and the uncertainties expressed in its pages about the state of American letters.